Solving Vibrating Spring Problem Using Variational Formulation - et. al., Ameera N. Alkiffai, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This scientific study is concerned with an integral equation, especially with Volterra integral equation and used new variational formulation which corresponds on the linear operator Lu=f. The vibrating spring equation has been solved using this approach.